2012
DOI: 10.3390/met2010022
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline Metal Hydrides Obtained by Severe Plastic Deformations

Abstract: It has recently been shown that Severe Plastic Deformation (SPD) techniques could be used to obtain nanostructured metal hydrides with enhanced hydrogen sorption properties. In this paper we review the different SPD techniques used on metal hydrides and present some specific cases of the effect of cold rolling on the hydrogen storage properties and crystal structure of various types of metal hydrides such as magnesium-based alloys and body centered cubic (BCC) alloys. Results show that generally cold rolling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 69 publications
1
17
0
Order By: Relevance
“…Further rolling passes resulted in a higher decrease of hydrogen capacity. This decay in hydrogen capacity for cold rolled samples may be associated to a distortion of interstitial sites due to excessive micro-strains accumulated ( Table 2) and/or excessive surface oxidation [8,9,13]. Szpunar et al [14] observed that deformation in Zircaloy play an important role on the hydride nucleation and orientation.…”
Section: Cold Rollingmentioning
confidence: 97%
“…Further rolling passes resulted in a higher decrease of hydrogen capacity. This decay in hydrogen capacity for cold rolled samples may be associated to a distortion of interstitial sites due to excessive micro-strains accumulated ( Table 2) and/or excessive surface oxidation [8,9,13]. Szpunar et al [14] observed that deformation in Zircaloy play an important role on the hydride nucleation and orientation.…”
Section: Cold Rollingmentioning
confidence: 97%
“…BCC alloys with body-centered cubic lattice (BCC lattice), for example in the Ti-V-Cr system, occupy a special place among the most promising materials for hydrogen storage [1][2][3]. They can absorb up to 3.8 wt.% of hydrogen in the favorable temperature range of hydrogen output, which is a key factor for their application in practice [4][5][6]. Recently, Ti-V-Cr alloys were also used as catalysts for magnesium alloys [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…They can absorb up to 3.8 wt.% of hydrogen in the favorable temperature range of hydrogen output, which is a key factor for their application in practice [4][5][6]. Recently, Ti-V-Cr alloys were also used as catalysts for magnesium alloys [5,7]. However, up till now these materials have mainly been saturated from the gas phase [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial H-sorption kinetics of cold rolled Mg-based alloys was systematically reviewed by Huot [22]. By comparing the kinetics of MgH 2 doped with transition metal oxides as catalysts, it was found that cold rolled samples possess relatively slower dehydrogenation kinetics compared to the milled counterparts, since atomic mixing is more difficult by CR than by HEBM [23].…”
mentioning
confidence: 99%